Biodiversity of Mites - Gwiazdowicz, Dariusz J. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The world of mites, being exceptionally diverse and rich, may be analysed both in historical and geographical terms. It is commonly known that these tiny, ubiquitous invertebrates are found both in terrestrial and aquatic ecosystems; additionally, they are relatively abundant in aeroplankton. The species composition and character of their assemblages vary, and they are different in the polar, temperate and tropical regions. All the above-mentioned factors force scientists to apply a unique approach to research problems and specifically define the aims of their investigations. The Diversity Special Issue on "Biodiversity of Mites" contains complex acarological issues including zoogeographic, ecological and parasitological research conducted in several regions of the world. The results of the presented research concern various taxonomic groups of mites occurring in both terrestrial and aquatic environments. Therefore, they can be an inspiration to search for new research directions and solve contemporary scientific problems.